Creative-aesthetic product design and tools. - Bertacchini, Francesca; Pantano, Pietro S.; Bilotta, Eleonora (Visual Resources: An International Journal of Documentation, 2022)
Providing a product with characteristics of beauty and creative innovation is one of the aims of any contemporary industry to meet the needs of customers and satisfy their aesthetic and functional requirements. To study the production process and the realisation of creative products with aesthetically pleasing attributes, we created an environment that allows the construction of simple textured polygons (triangles, squares, rhombuses and pentagons) through a software application. To overcome traditional ways of assessing creative products, a Birkhoff aesthetic measure, Euclidean distance and entropy measure have been developed and applied to a sample of smart products, manufactured in the implemented environment, to analyse their aesthetic, creative and order–complexity–chaos features, respectively. The results provided us with measurable quantities of the required qualities for the sample and for each distinct product, combining the metrics to visualise the creative products in 2D and 3D spaces. Further mathematical methods, such as the point process and density probability map applied on the same sample, allowed us to move from a statistical space to probabilistic landscapes, with enhanced forecasting capability on creative features for all future products. Industrial applications are expected in the production and evaluation of products from a creative point of view.